Health warnings on wine labels: A discrete choice analysis of Italian and French Generation Y consumers - Azzurra Annunziata; Lara Agnoli; Riccardo Vecchio; Steve Charters; Angela Carla Mariani (Wine Economics and Policy, 2019)
This paper aims to analyse Generation Y consumers' preferences for, interest in and attitudes towards different formats of health warnings on wine labels in two countries with different legal approaches: France and Italy. A Discrete Choice Experiment was realized on a sample of 500 wine consumers. Three warning options were applied: the long-term effect of drinking (brain damage); a short-term effect (car crash) and no warning option. Four attributes composed the choice set: alcohol content; framing of warning statement; warning size and position. Findings reveal that both the general degree of attention to the label and the level of visibility of the warnings are low, as are their effectiveness in changing consumption. Generation Y tend to prefer the "no logo option", short-term effects warnings and a small logo posted on the back label with neutrally framed messages. Results also show some significant differences among preferences in France and Italy, providing inputs to the ongoing debate in the EU on mandatory labelling. Although findings are subject to limitations related to the use of self-reported questionnaire and prone to social-desirability bias, practical implications are clear for private companies interested in implementing marketing strategies focused on enhancing the efficacy and readability of labels.
Keywords: 330; Health warning; Wine labelling; Discrete Choice Experiment